Advanced voltage balancing techniques for series-connected SiC-MOSFET devices: A comprehensive survey - Luciano F.S. Alves; Pierre Lefranc; Pierre-Olivier Jeannin; Benoit Sarrazin (Power Electronic Devices and Components, 2024)
This paper presents a comprehensive survey of voltage balancing techniques for series-connected SiC-MOSFETs. The concept of connecting power devices in series is appealing due to the potential to achieve higher block voltages using lower-voltage components. However, this approach comes with several challenges, particularly the uneven distribution of switching transitions among these power devices, which can lead to voltage balancing problems. In addition to presenting the factors that can influence the voltage balancing across the power devices, this work introduces the main existing voltage balancing techniques proposed to improve the voltage-sharing performance of series-connected SiC-MOSFETs.